Banking strategy, credit appraisal, and lending decisions a risk-return framework - Bhattacharyya, Hrishikes (New Delhi : Oxford University Press, 2011)
Hrishikes Bhattacharyya provides a comprehensive analysis of lending strategies, credit appraisal, risk analysis, and lending decisions within a risk-return framework.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Bank management -- India; Bank loans -- India; Credit ratings -- India; Banks and banking -- Risk management -- India